Will the poor of today be the poor of tomorrow? The determinants of poverty and vulnerability in Cartagena, Colombia (2010)
This paper examines the evolution and causes of poverty in Cartagena, Colombia, during the period 2002-2005. We use a probabilistic model (probit) to identify the individual characteristcs that explain the incidence of poverty in the city. We also examine the concept of vulnerability, defined as the possibility that future levels of consumption may be below the poverty line. We find that poverty by income has diminished but continues to affect a significant proportion of the local population